2014
DOI: 10.3390/d6020283
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Genetic Diversity in Forest Tree Populations Using Molecular Markers

Abstract: Molecular markers have proven to be invaluable tools for assessing plants' genetic resources by improving our understanding with regards to the distribution and the extent of genetic variation within and among species. Recently developed marker technologies allow the uncovering of the extent of the genetic variation in an unprecedented way through increased coverage of the genome. Markers have diverse applications in plant sciences, but certain marker types, due to their inherent characteristics, have also sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(59 citation statements)
references
References 93 publications
4
48
0
3
Order By: Relevance
“…An average of 0.31 was reported for Anonna crassiflora (Cota et al, 2011). The high values obtained in our study are quite encouraging and conform to that expected for tree species which generally present greater genetic variation within populations (Porth and El-Kassaby, 2014). The genetic similarity indices usually range from zero to one, with values closer to one indicating greater genetic diversity.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…An average of 0.31 was reported for Anonna crassiflora (Cota et al, 2011). The high values obtained in our study are quite encouraging and conform to that expected for tree species which generally present greater genetic variation within populations (Porth and El-Kassaby, 2014). The genetic similarity indices usually range from zero to one, with values closer to one indicating greater genetic diversity.…”
Section: Discussionsupporting
confidence: 88%
“…Apart from maintaining food and health security, a rich genetic diversity is a basic resource for improvement programs. It also helps the species to withstand different biotic and abiotic stresses under changing environmental conditions (Porth and El-Kassaby, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This pattern has been explained to be the result of long generation times, woody life forms, out-crossing mating system, high fecundity, mechanism of pollination (anemophily), long age and dispersal of seeds by animals. These are responsible for the low levels of differentiation between populations, which Shiran et al, 2011;QIN et al, 2012;Zhang et al, 2013;Alfonso-Corrado et al, 2014;Porth & El-Kassaby, 2014;ValenciaCuevas et al, 2014 andWang et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, mean H e across five common loci (WS00716.F13, WS0022.B15, WS0073.H08, WS00111.K13, WS0023.B03) was slightly higher (0.89) in Serbian populations in comparison to those observed in Tyrol (0.87) and the Czech republic (0.86) [47,48]. Numerous studies using SSRs evidenced that geographically widespread tree species showed significantly higher intra-population genetic diversity than variation among populations (e.g., [51,52]). Also here, the major proportion of gene diversity was harbored within populations, with only minor share partitioning among them.…”
Section: Discussionmentioning
confidence: 95%
“…Reed and Frankham [63] documented a strong positive correlation between heterozygosity and population fitness, which is important for the long-term adaptation of populations to novel environmental conditions. Besides heterozygosity, certain authors identified allelic richness as a more suitable parameter for conservation purposes [52,64,65]. Discussing selection of candidate populations for conservation based on molecular marker studies, Petit et al [54] stated that allelic richness should get priority over heterozygosity because it is highly dependent on effective population size and provides better information concerning past evolutionary history.…”
Section: Conservation Of Norway Spruce Forest Genetic Resources In Sementioning
confidence: 99%